2018
DOI: 10.20546/ijcmas.2018.706.394
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Genetic Diversity in Traditional Landraces of Rice for Yield and Its Attributing Traits under Saline Stress Condition

Abstract: Rice (Oryza sativa L.) is a one of the most important cereal crops and serves as the staple food for over one-third of the world's population (Chanbeni et al., 2012). The tremendous variation for salt tolerance within Oryza species provide opportunities to improve rice for salt-stress tolerance through genetic means.Soil salinization is a serious problem in the entire world and it has grown substantially causing loss in crop productivity (FAO, 2006). It is a major constraint limiting agricultural productivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Hence, these characters may be considered as principal discriminatory traits for this germplasm indicating that selection is effective in favour of these traits. Similar results were reported by Beevi and Venkatesan (2015) and Archana et al, (2018) for number of filled spikelets per panicle, Prasad et al, 2018 for spikelet fertility and 1000 seed weight, for grain yield per plant and 1000 grain weight by Sowmiya and Venkatesan (2017) for plant height, spikelet per panicle and grain yield /plant by Raghavendra et al, (2018).…”
Section: Principal Component Analysis (Pca)supporting
confidence: 86%
“…Hence, these characters may be considered as principal discriminatory traits for this germplasm indicating that selection is effective in favour of these traits. Similar results were reported by Beevi and Venkatesan (2015) and Archana et al, (2018) for number of filled spikelets per panicle, Prasad et al, 2018 for spikelet fertility and 1000 seed weight, for grain yield per plant and 1000 grain weight by Sowmiya and Venkatesan (2017) for plant height, spikelet per panicle and grain yield /plant by Raghavendra et al, (2018).…”
Section: Principal Component Analysis (Pca)supporting
confidence: 86%
“…Reductions in grain yield (Asch and Wopereis 2001;Abdullah et al 2001;Zeng et al 2002;Kiani et al 2006;Motamed et al 2008;Rao et al 2008;Clermont-Dauphin et al 2010;Mojakkir et al 2015;Raghavendra et al 2018) are particularly influenced by the number of panicles (Asch and Wopereis 2001) and panicle length (Abdullah et al 2001;Motamed et al 2008;Mojakkir et al 2015). Within-panicle characteristics affected by salinity include:…”
Section: Effects Of Salinity At the Reproductive Stage: Effects On Yield And Yield Componentsmentioning
confidence: 99%
“…Initially, attempts were made to understand the genetic basis of salt tolerance in legume and cereal crops [ 62 , 63 , 64 , 65 , 66 , 67 ]. Genetic and biostatistical studies on rice identified a few dominant genes governing salt tolerance in rice, and subsequent studies revealed the polygenic nature of the trait, involving both additive and non-additive gene actions [ 61 , 68 , 69 , 70 , 71 ]. Further studies found out that crop plants respond differently to salt stress in a growth stage-specific manner, making it more complex to understand the phenomenon.…”
Section: The Genetic Basis Of Tolerance To Salinity In Plantsmentioning
confidence: 99%